2020
DOI: 10.1371/journal.pone.0218634
|View full text |Cite
|
Sign up to set email alerts
|

Predicting factors for long-term survival in patients with out-of-hospital cardiac arrest – A propensity score-matched analysis

Abstract: Background Out-of-hospital cardiac arrest (OHCA) is one of the leading causes of death worldwide, with acute coronary syndromes accounting for most of the cases. While the benefit of early revascularization has been clearly demonstrated in patients with ST-segment-elevation myocardial infarction (STEMI), diagnostic pathways remain unclear in the absence of STEMI. We aimed to characterize OHCA patients presenting to 2 tertiary cardiology centers and identify predicting factors associated with survival.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Despite that, according to our study results, early PCI was an independent predictor of intrahospital survival and ECG showing STEMI upon admission was an independent predictor of good neurological outcome. Similar results were published by Lahmann et al in their recently published study of 519 patients hospitalized after OHCA, where they found that the 30day and 1-year survival rates were significantly higher among patients undergoing immediate coronary angiography compared to patients on whom immediate coronary angiography was not performed (221/370 (59.7%) vs. 30/131 (22.9%), p = 0.001) and that in patients on whom immediate coronary angiography was performed, a good neurologic outcome at discharge, defined as CPC 1 or 2, was achieved in 164/299 (54.8%) [12]. This is a very important finding since the benefit of early revascularization has been proven in patients with STEMI, while diagnostic pathways remain unclear in the absence of STEMI.…”
Section: Discussionmentioning
confidence: 93%
“…Despite that, according to our study results, early PCI was an independent predictor of intrahospital survival and ECG showing STEMI upon admission was an independent predictor of good neurological outcome. Similar results were published by Lahmann et al in their recently published study of 519 patients hospitalized after OHCA, where they found that the 30day and 1-year survival rates were significantly higher among patients undergoing immediate coronary angiography compared to patients on whom immediate coronary angiography was not performed (221/370 (59.7%) vs. 30/131 (22.9%), p = 0.001) and that in patients on whom immediate coronary angiography was performed, a good neurologic outcome at discharge, defined as CPC 1 or 2, was achieved in 164/299 (54.8%) [12]. This is a very important finding since the benefit of early revascularization has been proven in patients with STEMI, while diagnostic pathways remain unclear in the absence of STEMI.…”
Section: Discussionmentioning
confidence: 93%
“… 1 Extensive research has been conducted on factors associated with short-term survival following OHCA. 9 , 10 , 11 Recently, however, increased focus has been placed on the long-term outcomes of OHCA, 12 , 13 , 14 including long-term survival and health-related quality of life during the additional years of life lived, 12 , 15 , 16 , 17 which help evaluate the natural history and long-term impact of OHCA on the health burden of society. 12 , 18 , 19 To quantify both the fatal and non-fatal disease burden of OHCA, several recent articles had applied the concept of disability-adjusted life years (DALYs) to OHCA.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Although most research on cardiac arrest (CA) emphasizes situational differences such as witnessed arrest, bystander cardiopulmonary resuscitation, or shockable cardiac rhythm, little has been investigated into the relationship between prognoses and biomarkers. 8-12…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Although most research on cardiac arrest (CA) emphasizes situational differences such as witnessed arrest, bystander cardiopulmonary resuscitation, or shockable cardiac rhythm, little has been investigated into the relationship between prognoses and biomarkers. [8][9][10][11][12] Renal function has been suggested to predict patient outcomes in a few circumstances, including CA and acute coronary syndrome, as chronic kidney disease is notorious for increased cardiovascular risks. 13,14 The blood urea nitrogen (BUN) to creatinine (Cr) ratio (BCR) is a promising indicator reflecting more than patient fluid or nutritional status.…”
Section: Introductionmentioning
confidence: 99%